2020
DOI: 10.1007/s10641-020-01016-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of smallmouth bass predation on subyearling fall Chinook salmon over a broad river continuum

Abstract: Smallmouth bass (Micropterus dolomieu) predation on subyearling fall Chinook salmon (Oncorhynchus tshawytscha) was examined in the Snake River (USA) to identify seasonal and habitat-related changes in bass diets, and associated subyearling consumption and loss in various riverine and impounded reaches. Smallmouth bass diets reflected opportunistic foraging that at times showed predation on subyearlings is influenced by the consumption of other prey such as crayfish, sand roller (Percopsis transmontana), and sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…2015; Tiffan et al. 2020), managers will have to consider the tradeoffs of controlling adults and juveniles near the upstream extent versus the uncertainty of future spread and amplification of their consumptive impacts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2015; Tiffan et al. 2020), managers will have to consider the tradeoffs of controlling adults and juveniles near the upstream extent versus the uncertainty of future spread and amplification of their consumptive impacts.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Smallmouth Bass introductions in tributaries to the Columbia River ultimately resulted in invasions and substantial predation on juvenile salmonids across most of the lower and middle Columbia River basin, wherein widespread prevention of future spread may now be challenging (Carey et al 2011;Rubenson and Olden 2020). For nonnative species that were intentionally introduced but can have unintended consequences for fish assemblages (e.g., Smallmouth Bass and Rainbow Trout Oncorhynchus mykiss; Shelton et al 2015;Tiffan et al 2020), managers will have to consider the tradeoffs of controlling adults and juveniles near the upstream extent versus the uncertainty of future spread and amplification of their consumptive impacts.…”
Section: Implications For Upstream Range Expansionmentioning
confidence: 99%
“…Smallmouth Bass can cause significant predation mortality for ecologically and societally important native species like Pacific salmon Oncorhynchus spp. For example, Smallmouth Bass have been estimated to consume up to 35% of a Chinook Salmon O. tshawytscha smolt population as they migrate seaward, effectively reducing opportunities for fish to reach their adult life stage, where reproduction or harvest could occur (Fritts and Pearsons 2004;Sanderson et al 2009;Tiffan et al 2020). Watershed-scale Smallmouth Bass spatial distributions are strongly correlated with stream temperature, and anticipated range expansions under climate change are alarming in the context of increased potential for both predation and nonconsumptive impacts on Pacific salmon (Kuehne et al 2012;Lawrence et al 2014;Rubenson and Olden 2020;Marsha et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…2009; Tiffan et al. 2020). Watershed‐scale Smallmouth Bass spatial distributions are strongly correlated with stream temperature, and anticipated range expansions under climate change are alarming in the context of increased potential for both predation and nonconsumptive impacts on Pacific salmon (Kuehne et al.…”
Section: Introductionmentioning
confidence: 99%
“…These fish are widespread in habitats of juvenile Pacific salmon Oncorhynchus spp. throughout the Pacific Northwest, United States (Carey et al, 2011; Hughes & Herlihy, 2012; Rubenson & Olden, 2019; Tiffan et al, 2016) and have been shown to be a significant predation threat (Fritts & Pearsons, 2004; Tabor et al, 1993; Tiffan et al, 2020). Interactions between smallmouth bass and juvenile salmon increase during spring and summer as water temperature warms.…”
Section: Introductionmentioning
confidence: 99%